Reflections on the operation of the system of execution of punishments and security measures - Ruiz Hernández, Andrés Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This letter is intended to make a series of criticisms of how the systems of execution of penalties and security measures works in our country because the law governing is given serious contradictions and conflicts between different hierarchies and standards within the same standard that necessarily result in an obstacle for the proper functioning of the system, generating conflicts of jurisdiction among courts, between another troubles, sub tracting effectiveness, efficiency, validity and specially legitimacy. It is intended that the corollary of these criticisms serves as an invitation to reflect the system and its regulation and, therefore, aims for substantive changes in this area.